Incidence, Risk Factors, and Outcomes of Coronary Obstruction Following Valve-in-Valve Transcatheter Aortic Valve Replacement - Gao, Zhichun; Wang, Yong; Qian, Dehui; Jin, Jun (International heart journal, 2021)
There is scant information about the incidence, risk factors, and outcomes of coronary obstruction (CO) following valve-in-valve transcatheter aortic valve replacement (VIV-TAVR). A meta-analysis of the published studies from January 2000 to April 2020 was conducted, and the endpoint was CO. A total of 2858 patients were enrolled in this study. The mean age was 77.7 ± 9.8, and 39.9% of them were female. The Society of Thoracic Surgeons (STS) score, European System for Cardiac Operative Risk Evaluation (EuroSCORE), and Logistic EuroSCORE were 8.9 ± 7.8, 16.0 ± 10.9, and 26.3 ± 16.3, respectively. The overall incidence of CO was 2.58%. CO incidence between patients with prior stented and stentless valves were significantly different (1.67% versus 7.17%), with an odds ratio (OR) of 0.25 and a 95% confidence interval (CI) of 0.14-0.44 (P < 0.00001). The first-generation valves were significantly associated with higher CO incidence compared with the second-generation valves (7.09% versus 2.03%; OR, 2.44; 95%CI, 1.06-5.62; P = 0.04), while no statistical difference was found between self-expandable valves and balloon-expandable valves (2.45% versus 2.60%; OR, 0.99; 95%CI, 0.55-1.79; P = 0.98). Virtual transcatheter to coronary ostia (VTC) distance (3.3 ± 2.1 mm, n = 29 versus 5.8 ± 2.4 mm, n = 169; mean difference, -2.70; 95%CI, -3.46 to -1.95; P < 0.00001) and the sinus of Valsalva (SOV) diameter (27.5 ± 3.8 mm, n = 23 versus 32.3 ± 4.0 mm, n = 101; mean difference, -3.80; 95%CI, -6.55 to -1.05; P = 0.007) were enormously shorter in patients with CO. The 24-hour, in-hospital, and 30-day mortality of patients with CO were 10.5%, 30.8%, and 37.1%, respectively. In conclusion, device selections, VTC distances, and SOV diameters may be important factors in assessing the CO risk in VIV-TAVR.